Non-alcoholic fatty liver disease fibrosis score is a useful index for predicting all-cause mortality in patients with antineutrophil cytoplasmic antibody-associated vasculitis - Whang, Jeong Yeop; Park, Pil Gyu; Park, Yong-Beom; Huh, Ji Hye; Lee, Sang-Won (Frontiers in Medicine, 2023)
Background: This study investigated whether the non-alcoholic fatty liver disease fibrosis score (NFS) could predict all-cause mortality during follow-up among patients with antineutrophil cytoplasmic antibody-associated vasculitis (AAV). Methods: The medical records of 256 AAV patients were retrospectively reviewed. AAV patients with clinically critical chronic liver diseases were excluded. NFS was calculated using the following equation: NFS = -1.675 + 0.037 - age + 0.094 – body mass index + 1.13 × impaired fasting glucose/diabetes mellitus + 0.99 × aspartate aminotransferase/alanine aminotransferase ratio - 0.013 × platelet count - 0.66 × serum albumin. Results: The median age was 59.0 years, and 35.2% of the patients were male. The median Birmingham Vasculitis Activity Score (BVAS), five-factor score (FFS), and NFS were 12.0, 1.0, and -4.7, respectively. Of the 256 patients, 33 (12.9%) died. Using the receiver operating characteristic curve, the optimal cut-off of NFS for all-cause mortality was obtained as -3.97. AAV patients with NFS at diagnosis ≥-3.97 exhibited a lower cumulative patients’ survival rate than those with NFS at diagnosis <-3.97. The multivariable Cox analysis revealed that NFS at diagnosis ≥-3.97 (HR 2.232, 95% CI 1.011, 4.925) was independently associated with all-cause mortality in AAV patients. Conclusions: This study was the first to demonstrate that NFS at AAV diagnosis was clinically useful in predicting all-cause mortality during follow-up, regardless of both the degree of liver fibrosis and abnormal or normal liver function results.